Profiling Cell Wall Monosaccharides and Nucleotide‐Sugars from Plants. Issue 2 (12th June 2019) - Rautengarten, Carsten; Heazlewood, Joshua L.; Ebert, Berit
Abstract: The cell wall is an intricate mesh largely composed of polysaccharides that vary in structure and abundance. Apart from cellulose biosynthesis, the assembly of matrix polysaccharides such as pectin and hemicellulose occur in the Golgi apparatus before being transported via vesicles to the cell wall. Matrix polysaccharides are biosynthesized from activated precursors or nucleotide sugars. The composition and assembly of the cell wall is an important aspect in plant development and plant biomass utilization. The application of anion‐exchange chromatography to determine the monosaccharide composition of the insoluble matrix polysaccharides enables a complete profile of all major sugars in the cell wall from a single run. While porous carbon graphite chromatography and tandem mass spectrometry delivers a sensitive and robust nucleotide sugar profile from plant extracts. Here we describe detailed methodology to quantify nucleotide sugars within the cell and profile the non‐cellulosic monosaccharide composition of the cell wall. © 2019 by John Wiley & Sons, Inc.